2007
DOI: 10.4161/cc.6.16.4614
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the p53 Family for Cancer Therapy: ‘Big Brother’ Joins the Fight

Abstract: Inactivation of p53-mediated signaling plays a major role in both the genesis and therapy resistance of human cancer. Nearly all tumors contain mutations in p53 itself or have perturbations in the p53 pathway. Since there is clear evidence that many tumor cells are more likely to die in response to wild-type p53 activation or restoration than are their normal counterparts, there has been considerable interest in the development of small molecules that target p53 for therapeutic gain. These include compounds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 75 publications
(99 reference statements)
2
28
0
Order By: Relevance
“…The loss of p53 function allows cells with damaged DNA to continue to proliferate and, therefore, it is associated with tumor progression (14). There is increasing evidence supporting p53 as an attractive target in cancer therapy (15). Our results revealed that YBBEs treatment resulted in a dosedependent increase in p53 level.…”
Section: Discussionsupporting
confidence: 53%
“…The loss of p53 function allows cells with damaged DNA to continue to proliferate and, therefore, it is associated with tumor progression (14). There is increasing evidence supporting p53 as an attractive target in cancer therapy (15). Our results revealed that YBBEs treatment resulted in a dosedependent increase in p53 level.…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies show that p73 can be engaged to activate p53 apoptotic pathways in tumor cells that have mutated p53 (22). There has been substantial interest both in drugs that target p73 and in potential prognostic markers of p73 activity.…”
Section: Discussionmentioning
confidence: 99%
“…8 In response to DNA damage, p53 activates numerous downstream transcriptional targets involved in cell cycle arrest and apoptosis, such as p21, Puma, Bax, and Noxa. 9 The levels and activity p53 in the cell are largely regulated through its posttranslational modifications, such as ubiquitylation, phosphorylation, and acetylation. Monoubiquitylation of p53 can result in its export from the nucleus and its mitochondrial translocation, thus preventing it from acting as a transcription factor, while allowing it to induce mitochondrial mediated apoptosis.…”
Section: Pirh2 and P53mentioning
confidence: 99%